Pengenalan Otomasi Perpustakaan di Pesantren Darul Falah Muhammadiyah Malua Kabupaten Enrekang - Ismaya Ismaya (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
The school library is a supporting unit for teaching and learning activities, for this reason the library needs to provide various services that can be utilized by students and teachers. One of the services that is important to provide is library automation services. Library Automation is the utilization of information technology for activities in the library including procurement, processing, storage and dissemination of information. With the existence of an automation system in the library, it is hoped that the processing of library collection data will be faster and easier. This community service activity was carried out as an effort to introduce automation-based library services at the Darul Falah Muhammadiyah Islamic Boarding School library, Enrekang Regency. The activity was carried out for one (1) face-to-face day, namely Wednesday 13 July 2022. The participants in this activity were librarians, as well as all teaching and educational staff at the Darul Falah Muhammadiyah Islamic Boarding School, Enrekang Regency.